Penaeid prawn fishery and its maximum sustainable yield at Versova, Mumbai - Deshmukh, V D; Patkar, D S; Karnik, P C (Indian Journal of Fisheries, 2011)
Penaeid prawn fishery at Versova, Mumbai was investigated for the ten-yearperiod of 1988 to 1997. The average annual catch during the period was 3,764 t,of which the trawlers contributed 84.9% and 15.1% by the dol nets. The majorspecies contributing to the fishery were Parapenaeopsis stylifera (61.2%), Solenoceracrassicornis (12.4%), Metapenaeus affinis (8.9%) and M. brevicornis (8.5%)'intrawlers andP. stylifera (51.5%),S. crassicornis (28.3%) andP. hardwikii (11.0%)in dol nets. Month wise abundance, size range, mean size, maturity and sex ratioin the two gears averaged for the period are discussed. Trawling at Versovacommenced in 1986-'87 and due to encouraging returns many dol net owners alsoshifted over to trawling. Consequently the catch of penaeid prawns also increasedfrom 1,363.71 in 1988 to 4,740.71 in 1996, and thereafter it declined considerably.Using Schaefer's surplus yield model, maximum sustainable yield (MSY) andthe related effort (FMSY) were estimated. The MSY was found to be 4,368.81 withthe optimum effort of 3.75 X 105 hours of fishing for the dol nets and trawlerstogether, which corresponds to operation of 158 daily trawler trips and 38 dol netboats for the sustainable penaeid prawn fishery at Versova.